Access to higher education and career advancement for women in the South African work environment - Dosunmu, A.G.; Dichaba, M. (South African Journal of Higher Education, 2019)
Women are underrepresented in terms of access to higher education in sub-Saharan Africa. In contrast, six out of every ten first degree and 44% of PhD graduates in all disciplines were South African women. Yet, despite the number of South African women accessing higher education this has not really translated into career advancement in the workplace. Specifically, the paper seeks to understand how a higher education degree may facilitate the career advancement of women in the workplace. Two keys concepts underpin the study, namely, lifelong learning and human capital development (HCD). The conceptual framework is thus premised on an understanding that access to higher education for women is critical to HCD, which is a key factor if organisations are to improve their performance. Methodologically, the study used a mixed methods design. Face-to-face interviews were conducted with selected senior women managers and 234 questionnaires were administered to junior workers at a telecommunications organisation in South Africa in 2015. The findings point to the importance of lifelong learning in higher education for women as it assists in reducing gaps in income, accessing senior management positions and, thus, achieving their goals as women. Perhaps the most abiding idea that emerges is that the women in this study displayed a strong sense of ambition.